Nanobioconjugates for targeted delivery of antigenic and therapeutic peptides at colorectal cancer (2024)
ABSTRACT: Colorectal cancer (CRC) presents challenges due to the limited effectiveness and side effects of conventional treatments like chemotherapy and surgery. Nanobioconjugates, such as poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs), offer improved drug delivery alternatives. Peptides bonded to CRC receptors show potential as therapies and vaccines. This study encapsulates the P1 peptide in PLGA-PEG-Mal NPs, functionalized with the G3 peptide for targeted CRC cell delivery to inhibit cell proliferation1,2, and encapsulates the P2 peptide in PLGA-COOH polymer to inhibit tumor growth via CD8+ T-cell activation, using D-mannosamine for targeting antigen-presenting cells 3,4. By studying the physicochemical properties of PLGA and peptides, the research aims to enhance stability and controlled release while minimizing side effects and improving CRC therapy from nanobioconjugates and peptide synergies.